Quantifying the response of wheat (Triticum aestivum L) root system architecture to phosphorus in an Oxisol - Flavel, Richard J; Guppy, Christopher N; Tighe, Matthew K; Watt, Michelle; Young, Iain M (Plant and soil, 2014)
BACKGROUND AND AIMS: Despite the recognised importance of root architecture to plant productivity, our ability to easily observe and quantify root responses to stresses in soil at appropriate mechanistic resolution, remains poor. In this study we examine the impact of P bands on root architecture in heterogeneous soil, trialling a rapid non-destructive analysis technique. METHODS: We examined fast (<5 min), high resolution (69 μm voxels) x-ray tomography (μCT) to non-destructively observe and quantify wheat (Triticum aestivum L.) roots in a repacked Oxisol, in 3D, with and without a band of P-enriched soil. RESULTS: We found that wheat roots displayed localised responses (were plastic) and responded with additional root length within the banded P fertiliser. The seedling root systems also altered 3D root architecture in the band by increasing the number and length of branch roots. Branch root angle was not altered by the P band. The spatial precision of the branching response was striking and raises questions concerning the root sensing and/or response mechanisms.